Effectiveness of Rice Washing Water and Planting Media on Growth and Production of Strawberry Plants (Fragaria vesca L.) - Qorry Hilmiyah Harahap (Jurnal AGROHITA: Jurnal Agroteknologi Fakultas Pertanian Universitas Muhammadiyah Tapanuli Selatan, 2022)
The use of rice washing water and some planting media which are organic materials is one of the efforts to keep nutrients in the soil so that they are not damaged by the use of chemicals. This research uses factorial randomized block design (RAK), with two factors to be investigated, namely Rice Washing Water (A) consisting of 4 levels studied A0 = 0 ml / polybag (control), A1 = 150ml / polybag, A2 = 300 ml / polybag, A3 = 500 ml / polybag, and Provision of planting media (M) consists of 3 levels studied namely M1 = soil, M2 = soil + husk charcoal (1: 1), M3 = soil + cocopeat (1: 1 ). The parameters observed were plant height, number of leaves, number of fruits, fruit weight, and number of tillers. Significant influence on plant height parameters at ages 2, 4, 6 and 8 MST, number of leaves at 2, 4, 6 and 8 MST and number of fruits per first harvest sample also had a significant effect. From the results of statistical analysis the treatment of the planting median on the growth and production of the strawberry plants has a significant effect on all parameters of the measurement of strawberry plants.